UPACARA ADAT KEBO-KEBOAN DESA ALAS MALANG KECAMATAN SINGOJURUH KABUPATEN BANYUWANGI : (SUATU KAJIAN EKONOMI, SOSIAL, BUDAYA DAN RELIGI MASYARAKAT USING) - Dinna Eka Graha Lestari (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2020)
The Kebo-keboan traditional ceremony is one of the traditional ceremonies owned by the Using community in Banyuwangi Regency. The ritual of kebo-keboan aims to ward off disease outbreaks and ask God Almighty to be given safety and be kept away from the disturbances and trials that hit the community. At the traditional kebo-keboan ceremony, it is hoped that the future harvest will be increased or better than the previous harvest. This study aims to analyze the occurrence of the process of commodification of the Kebo-keboan traditional ceremony in Alasmalang Village, Singojuruh District, Banyuwangi Regency, the existence of a shift in meaning from religious to economic in the Kebo-keboan traditional ceremony in Alasmalang Village, Singojuruh Village, Banyuwangi Regency. This kebo-keboan traditional ceremony is still preserved and has a very important influence and position in the life of the Using community in Alasmalang Village. The kebo-keboan ceremony has an important position for the life of the people of Using Desa Alasmalang. The traditional kebo-keboan ceremony in Alasmalang Village has undergone commodification. In the implementation of the kebo-keboan ceremony, there are additional traditional Banyuwangi arts.